Depression in patients with diabetes mellitus and its relationship with the glycemic control - Andrés Vázquez Machado; Julienne Mukamutara (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: Some studies emphasize the presence of psychiatric signs in patients with diabetes mellitus. The depression is the most frequent mental disorder in diabetic patients; it is considered that 1 out of 3 patients with diabetes have depression and, in turn, the risk of having a depressive disorder is 2 times higher than in the general population.  Objective: To identify some factors associated with the depression in diabetic patients and their effect in the glycemic control.   Methods: A descriptive and cross-sectional study of 457 diabetic patients, assisted in the Central Hospital of Nampula, Mozambique, was carried out from March, 2014 to December, 2016.  As main variables we can mention: frequency of the depression symptoms, depressive disorders, sociodemographic characteristics, current vital events and glycemic control. The percentage was used as summary measure and as inference statistics the chi-squared test of independence and odds ratio, with a 95 % confidence interval.  Results: The frequency of depression symptoms and depressive disorders in the outpatient service was 32.3 and 24.3 %, respectively. The factors mostly associated with the depression were: the female sex, being widower or divorced and being a housewife. On the other hand, to experience 2 or more current vital events increased the depression probability and the latter was associated with a poor glycemic control  (p <0.05).   Conclusions: The frequency of depression in diabetic patients is high and it is associated with some sociodemographic variables, with current vital events and with a poor glycemic control.